Minyak Nilam sebagai Biofungisida untuk Pengendalian Penyakit Antraknosa Cabai - SakerebauDesni Roha Miriam; SoekarnoBonny Poernomo Wahyu Soekarno Poernomo Wahyu (Jurnal Fitopatologi Indonesia, 2014)
Anthracnose caused by C. capsici is the most important factor causing low yield on chili in Indonesia. A research was conducted to examine to examine the potential of patchouli oil in suppressing anthracnose disease development on chili. In vitro test was conducted by growing C. capsici on potato dextrose agar (PDA) medium that has been added with different concentration of patchouli oil, i.e. 10, 5, 2.5, 1.25 and 0.625%. Negative controls treatment (Kn) was conducted by growing C. capsici on PDA without patchouli oil, whereas positive controls (Kp) was conducted by growing C. capsici on PDA containing mancozeb fungicide. Patchouli oil -A significantly suppressed the growth of C. capsici compared to patchouli oil-B on 10 days after harvest, i.e. 91.15% suppression for all concentration level except for 0.625% which caused 85.92% suppression. Further examination using patchouli oil-A showed that incubation period on curative test was 8 days after inoculation (DAI) whereas on preventive and induced resistance test were 5 DAI. Disease severity at 10 DAI reached 4.8%, 23.20%, and 29.60% on curative, preventive, and induced resistance tests, respectively. Disease severity was 29.60% and 68.80% on positive control and negative control, respectively.